Seeking a Sense of Belonging: Social and Cultural Integration of International Students with American College Students - Rivas, Julia; Burke, Monica; Hale, Katherine (Journal of International Students, 2019)
International students studying at higher education institutions in the United States experience challenges as they adjust to new environments. Social connectedness to American college students could mitigate such challenges and assist international students with social and cultural integration. This study, using qualitative data from interviews, examined international students’ experiences and their sense of belonging on an American college campus, including the factors that contribute to or deter from it.